A contribution to assess the structural vulnerability timber pavements - Teixeira, Marcos (2014)
In general, timber pavements are the main horizontal structural elements of the Portuguese traditional buildings. Since these types of buildings required to be preserved, the maintenance of timber pavements is crucial. However and unfortunately, the demolition of the interior of traditional buildings still is a current building option in rehabilitation processes. This building scenario is more expressive in private estate, in particular, in private dwellings. This option may be due to the lack of technical knowledge concerning timber pavements. Therefore, this paper intends to give a contribution in this matter by proposing an expedite methodology able to assess the structural vulnerability of these types of horizontal structural elements. Mapping the different structural vulnerability degrees of a traditional timber pavement may give guidance for maintenance, inspection and/or reinforcement design processes.